Analysis of the Influence of Public Relations and Price Towards Consumer Buying Interest in Make-Up Artist Service (Case Study on Aliefiah Pranedya Make-Up Artist) - Aliefiah Pranedya (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
Make-up artist services is one of the businesses that lately is growing rapidly and has considerable growth potential. Marketing services such as make-up artist, running optimally when supported by structured planning It includes activities in the marketing mix of services that begin from identifying products as consumer needs that will be met, determining prices, promotional activities to be carried out, locations to market products to consumers, assigning people involved in business activities, as well as organizing processes to be used in business activities and also physical evidence. So the purpose of this research researchers want to find out more about public relations and prices can influence consumer buying interest in make-up artist services. This research is a quantitative research with the consumer population of women who have used the services of make-up artists in the city of Surabaya with an infinite number of population using Cosenza & Davis so that using 385 respondents with the criteria that is prospective consumers AP Make-up Artist female gender with a range of age 15-49 years and residents of Surabaya. The conclusion of this research is public relations factor and price influence on consumer purchasing interest in make-up artist services.